2022
DOI: 10.3390/su14138087
|View full text |Cite
|
Sign up to set email alerts
|

L2 Motivational Self System, International Posture and the Sustainable Development of L2 Proficiency in the COVID-19 Era: A Case of English Majors in China

Abstract: The L2 motivation self system (L2MSS) has been extensively researched in a variety of contexts, but few studies have delved into its relationship with international posture and the sustainable development of L2 proficiency in the COVID-19 era. To address this issue, we surveyed 156 English majors in China and analyzed their response data with structural equation modelling. The results show that the ideal L2 self positively predicts the L2 learning experience, while the ought-to L2 self has a negative predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…The IL2S, OL2S, and L2LE were also found to have a significant effect on English achievement. This finding is in accord with the recent study ( Zhao et al, 2022 ) reporting that L2 proficiency is positively influenced by L2LE and IL2S, but negatively impacted by OL2S. Similarly, the finding is also related to Papi’s study (2010) which revealed that OL2S significantly made L2 learners feel anxious, and the negative effect of anxiousness as a negative emotion on academic performance has been confirmed by several previous studies (e.g., MacIntyre, 1999 ; Gregersen and Horwitz, 2002 ; Horwitz, 2010 ; Dewaele and MacIntyre, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…The IL2S, OL2S, and L2LE were also found to have a significant effect on English achievement. This finding is in accord with the recent study ( Zhao et al, 2022 ) reporting that L2 proficiency is positively influenced by L2LE and IL2S, but negatively impacted by OL2S. Similarly, the finding is also related to Papi’s study (2010) which revealed that OL2S significantly made L2 learners feel anxious, and the negative effect of anxiousness as a negative emotion on academic performance has been confirmed by several previous studies (e.g., MacIntyre, 1999 ; Gregersen and Horwitz, 2002 ; Horwitz, 2010 ; Dewaele and MacIntyre, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to the most recent study by Basir and Kolahi (2022), each component of the L2MSS had no discernible influence on students' academic resilience. Zhao et al (2022) revealed that the ought-to L2 self had a detrimental analytical effect on the learner's academic performance. Then, Martinovic and Buric (2021) discovered that there were no discernible correlations between students' success in language learning and their motivating self-system in an L2.…”
Section: Discussionmentioning
confidence: 99%
“…To collect the data, we disseminated a set of questionnaires on the L2MSS (Dornyei, 2005) to students of a private Islamic boarding school in Malang, Indonesia. This survey instrument was also selected by many scholars (Bobkina et al, 2021;Jiao & Liang, 2022;Lee & Lee, 2019;Zhao et al, 2022) to measure the learners' motivation level in their research study. The L2MSS which was constructed by Dornyei (2005) has been employed in more than 40 research studies (Boo et al, 2015).…”
Section: Data Collection and Analysis Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the world has witnessed a change not seen for centuries. The outbreak of the COVID-19 pandemic has hindered the sustainable development of second language learning and quality education [42]. This change has made second language learning increasingly complex and uncertain, and traditional theories have made it hard to fully explain students' motivation for second language learning in the new era.…”
Section: Motivation Compositionmentioning
confidence: 99%